10. CLINICAL AND PARACLINICAL EPIDEMIOLOGICAL CHARACTERISTICS AND SOME FACTORS RELATED TO THE SEVERITY OF ADENOVIRUS-INFECTED PNEUMONIA AT THE RESPIRATORY DEPARTMENT OF NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical and paraclinical epidemiological characteristics of Adenovirus-infected pneumonia at the Respiratory Department of Nghe An Obstetrics and Pediatrics Hospital and comment on some factors related to the severity of Adenovirus-infected pneumonia.Research methods: Descriptive cross-sectional study.Results: Children from 2 to under 12 months old accounted for the highest proportion with 41.3%. Male/female ratio = 1.88. The majority of children reside in rural areas (87.0%). Most children contracted the disease in winter - spring. The main source of infection originated from the community (69.5%). Before admission, 73.9% of children had respiratory tract infections, diarrhea (10.9%), and vomiting (10.9%). All children had cough (100%), fever (84.8%), and conjunctivitis (6.5%). 100% were fully vaccinated, 13.0% were premature, 4.3% were malnourished, and 67.4% were anemic. All children had moist rales (100%), wheezing (91.3%), rapid breathing (71.7%), cyanosis (39.1%), chest retraction (60.8%), and wheezing and snoring (41.3%). The average number of days of treatment was 14.2 ± 9.2 days. Leukocytes increased in 65.2% of children. Platelets were mostly normal (69.6%). The majority of children had increased CRP (80.4%). 73.9% of children had scattered lung opacities on X-ray. Of the 10 cases of co-infection, 4 were co-infected with Haemophilus influenzae (40.0%), 3 were influenza A virus (30.0%), 2 were respiratory syncytial virus (20.0%) and 1 was Moraxella Catarrhalis (10.0%). Some factors related to the severity of adenovirus pneumonia were age, co-infection status and anemia.Conclusions: Some factors related to the severity of Adenovirus pneumonia are age, co-infection and anemia.
Keywords: Adenovirus pneumonia; co-infection; severe severity